A heuristic evaluation of a mobile annotation tool - Cunha, Bruna Carolina Rodrigues; Neto, Olibário J. Machado; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
Modern mobile devices are natural multimedia devices that enable one to access, manage and transmit multiple types of media such as video, photo, audio and maps. Video playing on these devices is becoming part of everyday life for many users. Aiming to enhance the video playback activity, we built a tool that allows temporal video annotation on mobile devices: text, audio and digital ink annotations can be added to the video using Android-based tablets and smartphones. Annotations can be passed along users through the sharing options available on the devices. We conducted a heuristic evaluation with ten experts and the results are discussed in this paper. Two different sets of heuristics were used to find a wider collection of issues. One of them is proposed by us and was developed especially for mobile devices. With this work, we expect to contribute with the theme of authoring on mobile devices in terms of user interface and evaluation.